Effect of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Tischhauser, Lyndy M.; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Newborn piglets are more susceptible to iron deficiency due to inadequate iron stores at birth and rapid growth rate before weaning. This causes fewer circulating red blood cells, lethargy, and mortality (Mateos, 2012). Gleptpforte is an injectable iron that contains gleptoferron and is utilized to prevent anemia in newborn piglets. There is limited data available that confirms the appropriate level of iron injection needed with modern genotypes. Therefore, the objective of this experiment was to evaluate the effect of increasing dosage of Gleptoforte in newborn pigs on sow and litter performance. A total of 336 newborn pigs (DNA 241 x 600, initially 3.83 ± 0.114 lb BW) were utilized in a 21-d farrowing experiment. A total of 28 litters were utilized with number of pigs per sow equalized on each day of farrowing. Three days after birth, all piglets were weighed and six barrows and six gilts per liter were allotted to one of six treatments for a total of 56 piglets per treatment. Treatments include 1) Negative control of no iron injection 2) 50 mg iron injection 3) 100 mg iron injection 4) 150 mg iron injection 5) 200 mg iron injection 6) 200 mg iron injection plus a 100 mg booster at d 11 of farrowing. Each 1 ml of Gleptoforte contained 200 mg of iron; injection dosage of Gleptoforte were 0, 0.25, 0.50, 0.75, 1.0, or 1.0 plus the 0.50 ml booster for each treatment. Overall, ADG and d 21 BW improved (quadratic; P = 0.001) with increasing dosage of Gleptoforte. However, there was no evidence of performance differing in any response criteria between treatments 5 and 6. On d 3 prior to the iron injection, there was no evidence of difference observed for any hematological criteria measured. On d 21, treatment 6 had a greater (P = 0.011) Hemoglobin value compared to treatment 5. In summary, a lack of iron injection resulted in the poorest growth and blood parameters of iron status of suckling piglets as expected. However, the administration of 100 mg of Gleptoforte resulted in the greatest growth performance. Finally, the administration of 200 mg + 100 mg of Gleptoforte resulted in improved hematological criteria but did not influence suckling piglet growth performance compared to 200 mg alone.
Keywords: Fall 2017